Plan de Negocios para el Desarrollo Turístico en la Finca de las Hermanas Hurtado, Parroquia la Tingue del Cantón Olmedo, Provincia de Loja - Uchuari Abrigo, Sonia Patricia (2017)
For the realization of this thesis work entitled "BUSINESS PLAN FOR TOURIST DEVELOPMENT IN THE FARM OF THE SISTERS HURTADO, LA TINGUE TOWN OF THE CANTON OLMEDO, LOJA PROVINCE", it was proposed as a general objective, to prepare a Business Plan for the Tourism development in the farm of the Sisters. Hurtado, La Tingue town of the Cantón Olmedo, Loja province, the same that took place through the accomplishment of three specific objectives which consisted in: first, to make a tourist diagnosis of the current situation in the Estate of the Sisters Hurtado; Second, to structure the proposal of business plan for the tourist development in the farm of the Sisters Hurtado, La Tingue town of the Cantón Olmedo, Loja province, and thirdly socialize the proposed Business Plan with the owners and relevant authorities. The methodology used for the development of research is related to the methods: scientist, deductive, inductive, analytic, descriptive and statistical, as well as techniques: literature review, observation, interview, survey and MARPP. Also used cards them attractions of MINTUR inventory and summary sheets to describe and evaluate the existing in the study area and their environment natural and cultural tourist attractions, settled with the SWOT analysis and the array of strategies. The result obtained in the Diagnostics tourism is reflected in six strategic objectives, serving as basis for the fulfilment of the business plan proposal. The second objective is structured in several studies as the market where discussed the supply, demand and the marketing mix; the technical study determined the size and location of the project, as well as the administrative study was planned the legal Constitution and the organizational structure of the farm; the financial study analysed the initial investment needed for the start-up of the business with $28.748,45 dollar, whose financial evaluation indicates a NPV of $12.119,84 dollar, TIR of 25.73%; a R b/c of 36 cents from utility with a PRC for 3 years, 11 months and 12 days, given in a sensitivity of 16.37% the increase in costs and 12.04% decrease in revenues; Finally, in the identification and evaluation of environmental impacts was obtained a total weighting of - 20 showing a minor impact. As a result of socialization, it was determined that the proposal is a starting point to boost tourist activity in the sector. After completion of the work in all its stages concludes the viability and feasibility of the business plan, so it is recommended to the various public and private institutions to support this initiative, since that way you can contribute to solving economic and social problems facing the population.